Creative industries, new business formation and regional economic growth - Roberta Piergiovanni; Martin A. Carree; Enrico Santarelli (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
The present study explores the impact exerted by a series of factors and processes including creativity, IPR activities, new business formation and the provision of amenities on economic growth for 103 Italian provinces (NUTS 3) over the period between 2001 and 2006. Provincial growth rates are measured alternatively by value added growth and employment growth. Findings show a positive effect of the increase in the number of firms active in the creative industries, net entry, and a greater provision of leisure amenities on regional economic growth. A large portion of employment in the manufacturing, mining, and energy sector, and a high relative number of university faculties are found to lead to slower economic growth, whereas trademarks, patents, cultural amenities and industrial districts do not affect economic growth. Finally, the share of legal immigrants is found to have a positive impact on employment growth.
Keywords: O18; O34; R11; 330; Regional growth; creativity; entrepreneurship; Italian provinces; Kreativsektor; Unternehmensgründung; Unternehmer; Regionales Wachstum; Beschäftigungseffekt; Italien